The effect of locus of control orientation on perceived individual innovativeness: An empirical research in Turkey - TÜRKER, MALİK VOLKAN; İNEL, MEHMET NURİ (ELSEVIER SCIENCE BV, 2012)
The aim of this study is to measure the effect of locus of control (LOC) orientation on perceived individual innovativeness in Turkey. A second aim is to try to find the possible role of gender in this relation. In order to test the propositions, a field survey using questionnaires was conducted in a sample of 314 undergraduate students enrolled at Marmara University, Turkey. Results indicated that there was a significant negative relationship between external locus of control and level of perceived individual innovativeness. A significant difference between female and male students on the relation between individually perceived LOC orientation and innovativeness was also found.
Keywords: Locus of control; individual innovativeness; Turkey; GENDER-DIFFERENCES; CONTROL SCALE; RELIABILITY; VALIDITY